2001
DOI: 10.1093/annonc/12.suppl_2.s159
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between neuroendocrine features and prognostic parameters in human prostate adenocarcinoma

Abstract: These data support the concept that NE differentiation in human prostate cancer has a negative prognostic significance. Circulating CgA levels reflect immunohistochemical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
2
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 23 publications
3
33
2
2
Order By: Relevance
“…Immunohistochemistry is highly specific, but its sensitivity may be influenced by sampling errors. The observed correlation between immunohistochemical CgA and pathological Gleason score, possibly reflecting the increased invasiveness of tumors with NED, is in agreement with Bollito's conclusions (18). In our series a significant correlation was found between preoperative serum CgA levels and either pathological tumor stage or pathological Gleason score.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Immunohistochemistry is highly specific, but its sensitivity may be influenced by sampling errors. The observed correlation between immunohistochemical CgA and pathological Gleason score, possibly reflecting the increased invasiveness of tumors with NED, is in agreement with Bollito's conclusions (18). In our series a significant correlation was found between preoperative serum CgA levels and either pathological tumor stage or pathological Gleason score.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to what has been reported by others (7,18,23), we were unable to find a significant correlation of preoperative serum CgA and its immunohistochemical expression with serum PSA, thereby suggesting a different behavior of neuroendocrine cells with respect to the (24,25), serum NSE in our series did not seem to be a useful tumor marker of NED in organ-confined CaP. Our data are in line with those reported by Slodkowska et al, who stated that NSE expression in the tumor and a mild increase in serum NSE are poor markers for distinguishing NED in non-small cell lung carcinomas (26).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The major point of this manuscript is to demonstrate that despite apparent loss of Bcl-2 protein expression, cells are still androgen-independent and apoptosis-resistant (DU-145 and specimens from patients with androgen-independent prostate cancer). Bcl-2 protein expression was regained in LNCaP-UR NE cells after extended growth in charcoal-stripped serum suggesting that NE-like cells, which are commonly found localized with high-grade tumors 22 may contribute to the progression to androgen-unresponsiveness in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Two recent studies in patients with hormone-refractory disease have demonstrated an independent poor prognostic role of elevated levels of circulating chromogranin A, a marker of neuroendocrine differentiation, 8,9 although in patients with hormone naive disease a significant relationship between amount of neuroendocrine cells and disease stage and grade but not with disease-free survival and overall survival has been unequivocally proven. [10][11][12] Neuroendocrine differentiation regulatory mechanisms might play a role in the transition from an androgen-dependent to an androgen-resistant phenotype in prostate cancer, and in vivo studies, both in animals 13 and humans, 14 have shown that the neuroendocrine prostate cancer compartment increases after androgen deprivation.…”
mentioning
confidence: 99%